Analisis Pondasi Tiang Pancang Pipa Baja Jembatan Parit 3 Kec. Kuala Jambi - Muhamad Ardy Pratama; Suhendra Suhendra; Dwitya Okky Azanna; Amsori M. Das; Wari Dony; Fadlan Fadlan (Universitas Batanghari Jambi, 2026)
Steel pipe pile foundations function to transfer superstructure loads to the supporting soil layer while providing resistance to axial and lateral forces. These foundations are widely used not only for buildings but also for various civil engineering structures, including bridges. The Parit 3 Bridge in Kuala Jambi District was constructed to reconnect two disconnected road sections, thereby improving local community accessibility. This study aimed to analyze the bridge structural loading and determine the bearing capacity of the steel pipe pile foundation using the Schmertmann and Nottingham method. Bridge loading calculations were performed in accordance with SNI 1725:2016, while the foundation bearing capacity was evaluated using the Schmertmann and Nottingham method. The results indicated that the maximum factored ultimate load under the Strength 1 load combination was Pu = 3,695.00 kN, equivalent to 376.79 tons. The allowable bearing capacity of a single pile was Qa = 739.538 kN, equivalent to 75.411 tons, whereas the bearing capacity of the pile group was Qg = 7,395.380 kN, equivalent to 751.841 tons. The calculated pile group bearing capacity exceeded the maximum applied load, indicating that the foundation satisfied the required bearing capacity criteria. Furthermore, both the single-pile settlement and the pile-group settlement were smaller than the allowable settlement, demonstrating that the settlement requirements were also satisfied.